Transgressão dos limites disciplinares através de comunidades de afeto e redes de conhecimento - Rodriguez, Breno Lima (2013)
The discourse erected in education in the hard sciences is still rooted strung on Cartesian method, in which the whole is equal to the sum of its parts. The move echoes caused by this contribution in the educational process favoring practices with quantitative traits in the speech of the place-teacher, based on a molar line, surpasses any voices that might challenge the construction of knowledge enthroned by the academy. In search of other possible that can happen within these practices try using the method of the conversations, systematic and non-systematic, have a glimpse about how students IFES, Victoria campus, build their networks of subjectivity / affectivity in relation learning / knowledge of science. In this journey, the main theoretical, perfazemos an encounter with Deleuze and Guattari in their work apart and together; Latour, in their discussions of the science, and Carvalho in his studies on affection and expansive networks of commonalities in educational processes may enhance the construction of a life ruled an ethical-aesthetic movement. In these slides the students realize that, even with their notions impregnated by the molar speech, they envision plenty of potency in the educational process, its potential for growth, but also consider the ways employed by most teachers make relationships woven with science are away from their life, and, as locus research is a school whose main activity is professional education, theirs speeches feed mainly on the dichotomy applied science x pure science, and, just this last they associate to the classroom, a language that most do not think capable of mastering, and it is reserved for an esoteric caste whose teachers are inserted. Thus, we seek an answer, partial and transient, not in order to establish another dominant discourse, otherwise strength, problematize both science as a language as a place of slipping into a form-changing teacher, who engages in the discourse of students considering the relationship established by them within the scientific discourse, seeking clues to a minor science and teacher.